SHARPER-enhanced benchtop NMR: improving SNR by removing couplings and approaching natural linewidths. Issue 36 (14th April 2022) - Dickson, Claire L.; Peat, George; Rossetto, Matheus; Halse, Meghan E.; Uhrín, Dušan
Abstract : A signal enhancement acquisition and processing strategy for benchtop NMR producing 10 to 30 fold signal-to-noise increases is presented. Abstract : We present a signal enhancement strategy for benchtop NMR that produces SNR increases on the order of 10 to 30 fold by collapsing the target resonance into an extremely narrow singlet. Importantly, the resultant signal is amenable to quantitative interpretation and therefore can be applied to analytical applications such as reaction monitoring.